1999
DOI: 10.1177/026765919901400605
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenator thrombosis: an international phenomenon

Abstract: Oxygenator thrombosis, despite adequate anticoagulation, has become a recent concern amongst perfusionists worldwide. The phenomenon is characterized by a transient increase in oxygenator inlet pressure of up to 900 mmHg about 10-15 min after the institution of cardiopulmonary bypass (CPB). Depending on the size and location of the thrombus, shunting may occur that compromises gas transfer to the extent where oxygenator change-out is necessary. This article presents various case reports and publications, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 22 publications
2
34
1
Order By: Relevance
“…Thus, any further reduction in these channels' dimensions, caused by depositions, would cause a marked increase in resistance to blood flow and an increase in transmembrane pressure. 6 It has also been noted that these pressure gradients are not limited to low-prime oxygenators, but that this phenomenon is more pronounced and occurs sooner in these than in higher-prime oxygenators. 5,6 Others have suggested that these increases in transmembrane pressures are caused by the activation of platelets and their subsequent deposition with fibrinogen on the membrane surface.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, any further reduction in these channels' dimensions, caused by depositions, would cause a marked increase in resistance to blood flow and an increase in transmembrane pressure. 6 It has also been noted that these pressure gradients are not limited to low-prime oxygenators, but that this phenomenon is more pronounced and occurs sooner in these than in higher-prime oxygenators. 5,6 Others have suggested that these increases in transmembrane pressures are caused by the activation of platelets and their subsequent deposition with fibrinogen on the membrane surface.…”
Section: Discussionmentioning
confidence: 97%
“…6 It has also been noted that these pressure gradients are not limited to low-prime oxygenators, but that this phenomenon is more pronounced and occurs sooner in these than in higher-prime oxygenators. 5,6 Others have suggested that these increases in transmembrane pressures are caused by the activation of platelets and their subsequent deposition with fibrinogen on the membrane surface. Aniuk et al have noted that many of these occurrences have been associated with the use of hydroxyethyl starches in the CPB priming solution.…”
Section: Discussionmentioning
confidence: 97%
“…Over the past few years, the phenomenon of HPE has been well documented 14,19,20 in the absence of albumin. It has been shown to occur in all oxygenators, with all primes and probably in all centers 15,20 when albumin is eliminated from the prime.…”
Section: Partmentioning
confidence: 99%
“…Currently, one of the major challenges in ECC device design is the minimization of flow-induced platelet activation, which is a major precursor of thromboembolic complications (Schaadt 1999). In comparison with hemolysis, platelet activation is responsible for the onset of thrombogenic phenomena that occur at shear stresses ten-fold lower than those responsible for red blood cell damage (Ramstack et al 1979).…”
Section: Introductionmentioning
confidence: 99%